2017
DOI: 10.1101/cshperspect.a028381
|View full text |Cite
|
Sign up to set email alerts
|

Big Bang Tumor Growth and Clonal Evolution

Abstract: The advent and application of next-generation sequencing (NGS) technologies to tumor genomes has reinvigorated efforts to understand clonal evolution. Although tumor progression has traditionally been viewed as a gradual stepwise process, recent studies suggest that evolutionary rates in tumors can be variable with periods of punctuated mutational bursts and relative stasis. For example, Big Bang dynamics have been reported, wherein after transformation, growth occurs in the absence of stringent selection, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 96 publications
4
35
0
Order By: Relevance
“…This model places macro-cellular evolution (where genome re-organization dominates) prior to micro-cellular evolution (where cancer gene mutation promotes population growth) and emphasizes the importance of CIN for generating new cancer genomes. This model fits well with both karyotype data and sequencing data from various cancer models [ 3 , 10 , 21 , 71 , 79 , 80 , 81 , 82 , 83 ]. More validation experiments are needed to examine this model.…”
Section: Conclusion and Future Perspectivesupporting
confidence: 52%
“…This model places macro-cellular evolution (where genome re-organization dominates) prior to micro-cellular evolution (where cancer gene mutation promotes population growth) and emphasizes the importance of CIN for generating new cancer genomes. This model fits well with both karyotype data and sequencing data from various cancer models [ 3 , 10 , 21 , 71 , 79 , 80 , 81 , 82 , 83 ]. More validation experiments are needed to examine this model.…”
Section: Conclusion and Future Perspectivesupporting
confidence: 52%
“…Importantly, however, the presence of numerous heterogeneous or private driving mutations in both precursor and endometrial carcinoma populations, most at clonal CCF, indicates a fitness advantage to these mutations regardless of histologic appearance or spatial proximity. Phylogenetic analysis thus supports extensive branched evolution in both precursor and endometrial carcinoma populations, consistent with branched evolution in LGEC development, in agreement with mechanisms in most other profiled cancers (23,24).…”
Section: Clonal Sweep Of Heterogeneous Mutations Is Common In Lgecsupporting
confidence: 74%
“…To the best of our knowledge, to date no information is available on phenotypic heterogeneity within primary breast cancer with respect to functional signaling pathway activity. Knowledge on signaling pathway heterogeneity is limited to studies on variations in ER and HER2 IHC staining, and on spatial variations observed in specific gene mutations and copy number changes across the tumor (17,18,(34)(35)(36)(37). However, this does not provide information on variations in functional signaling pathway activity.…”
Section: Within Tumor Heterogeneity Of Signaling Pathway Activitymentioning
confidence: 99%
“…Similar problems exist when choosing targeted therapy for treatment of patients with metastatic disease, where therapy choice is generally based on analysis of a tissue sample from the PT, although marked genotypic and phenotypic differences between PT and distant site (DS) metastases have been described (15,16). Unfortunately, limited knowledge is available on heterogeneity in signaling pathway activity within a PT and between PT and LN and DS metastases (17,18). One reason has been lack of reliable assays to measure signaling pathway activity in formalin fixed paraffin embedded (FFPE) tissue samples used in the routine diagnostic setting.…”
Section: Introductionmentioning
confidence: 99%